EVALUASI KINERJA UTAMA PEMERINTAH KABUPATEN BEKASI PROVINSI JAWA BARAT - Dedi Supriyadi; Dahyar Daraba; Halilul Khairi; Sutiyo Sutiyo (Jurnal Academia Praja, 2024)
This research discusses the misalignment between strategic planning and annual planning in achieving key performance indicators (KPIs) at the national and regional levels, with a focus on Bekasi District, West Java. This alignment is critical to achieving community welfare. Gaps were found between the performance targets in the National Medium-Term Development Plan (RPJMN) and the Government Work Plan (RKP), especially on economic growth, poverty levels, and unemployment. An evaluation of the KPIs in Bekasi District also showed non-optimality, with a number of KPIs not achieved. Qualitative research methods were used to evaluate this. Clear KPI establishment, accurate data collection, regular monitoring, and root cause analysis are important steps in KPI evaluation. The results show that the KPI setting process in Bekasi District still does not fulfill the SMART (Specific, Measurable, Assignable, Realistic, Time Related) criteria thoroughly.There are weaknesses in senior management commitment, an unoptimized performance culture, and a lack of Critical Factor Success (CSF) approach in the formulation of performance indicators.In addition, the process of simulating the achievement of KPIs and midterm evaluation of the RPJMD was not adequately implemented; however, this process was not fully followed at both the national and regional levels. In addition, the process of simulating the achievement of KPIs and the midterm evaluation of the RPJMD were not adequately implemented. However, this process was not fully followed at both the national and regional levels.